Sarcopenia in liver cirrhosis. Issue 3 (March 2015) - Giusto, Michela; Lattanzi, Barbara; Albanese, Carlina; Galtieri, Alessia; Farcomeni, Alessio; Giannelli, Valerio; Lucidi, Cristina; Di Martino, Michele; Catalano, Carlo; Merli, Manuela
<x xml:space="preserve">Abstract</x> Background Sarcopenia evaluated by computed tomography (CT) scan at the lumbar site has been identified as a risk factor for morbidity and mortality in cirrhosis. Aim The aim of this study was to compare the measurement of muscle mass through CT scan, considered the gold standard, with other reliable techniques to evaluate the rate of agreement between different available methods for the assessment of muscle mass in cirrhosis. The correlation between measurements of muscle mass and of muscle strength was also investigated. Patients and methods Adult patients eligible for liver transplantation were studied. Lumbar skeletal muscle cross-sectional area was measured by CT and muscle depletion was defined using previously published cut-offs. Mid-arm muscle circumference was calculated following anthropometric measures. The Fat-Free Mass Index and the Appendicular Skeletal Muscle Index were calculated using dual-energy X-ray absorptiometry. Muscle strength was evaluated using the Hand Grip test. Results Fifty-nine patients with cirrhosis were included. Sarcopenia was diagnosed in 76% of the patients according to CT evaluation. A significant reduction in Fat-Free Mass Index and Appendicular Skeletal Muscle Index was observed in 42–52% of the patients, whereas 52% showed a mid-arm muscle circumference less than 10th percentile. Skeletal muscle mass evaluation through CT was only weakly correlated with dual-energy X-ray absorptiometry and anthropometry evaluation. No correlation was observed between CT measurement of muscle mass and Hand Grip test. Conclusion CT scan can identify the highest percentage of sarcopenia in cirrhosis and no other techniques are actually available as a replacement. Future efforts should focus on approaches for assessing both skeletal muscle mass and function to provide a better evaluation of sarcopenia in cirrhotic patients.